2019
DOI: 10.3390/molecules24091770
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Use of Mesoporous Carbon and Mesoporous Silica as Drug Carriers for Oral Delivery of the Water-Insoluble Drug Carvedilol

Abstract: Mesoporous carriers have been extensively applied to improve the dissolution velocity and bioavailability of insoluble drugs. The goal of this work was to compare the drug-loading efficiency (LE) and drug-dissolution properties of mesoporous silica nanoparticles (MSN) and mesoporous carbon nanoparticles (MCN) as drug vectors oral delivery of water-insoluble drugs. For this purpose, MSN and MCN with similar particle size, surface area, and mesoporous diameter were prepared to precisely evaluate the effects of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…This observation can be explained by most Pip molecules being entrapped inside pores on the surface of HAPs. These results are in agreement with reports of loading drugs in mesoporous nanoparticles [30,31,63]. Changing the crystalline state of a water-insoluble drug to the non-crystalline state using mesoporous materials can enhance solubility, increasing the drug therapeutic activity [64].…”
Section: Discussionsupporting
confidence: 92%
“…This observation can be explained by most Pip molecules being entrapped inside pores on the surface of HAPs. These results are in agreement with reports of loading drugs in mesoporous nanoparticles [30,31,63]. Changing the crystalline state of a water-insoluble drug to the non-crystalline state using mesoporous materials can enhance solubility, increasing the drug therapeutic activity [64].…”
Section: Discussionsupporting
confidence: 92%
“…However, the control of particle size, specifically below 200 nm, remains challenging, due to the easy tendency of MSNs to aggregate. Indeed, MSN size regime between 50–200 nm, together with monodispersity, controlled pore size, shape and surface chemistry, represent essential features for biomedical application of MSNs as drugs and contrast agent vehicles [ 24 , 25 ]. Several studies have showed that efficiency of the cellular uptake and possibility to penetrate through the membranes/tissue are strongly dependent on particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ethanol can be easily and rapidly eliminated using rotary evaporation. The amount of phenolic extract to be loaded (phenolic extract:Syloid ® AL-1, 30:70, w / w ) was chosen on the basis of the values reported in the literature for different drugs and Syloid ® AL-1, and other mesoporous silicas having comparable surface area [ 26 , 32 , 33 ]. A theoretical loading of 30% ( w : w ) allows obtaining a final product where the phenolic extract is completely adsorbed and included in the pores of the mesoporous silica.…”
Section: Resultsmentioning
confidence: 99%